Decisions on Additional Counters in the Banking Industry and Applications of the Queuing Theory - Seow, Hsin Vonn (2000)
Many researchers have long explored the effects of customer waiting time on service level. In Malaysia, however, the effects of this particular issue have seldom been explored. This study was conducted to reduce this gap by examining the relationship between the waiting time and customer satisfaction level in Malaysia's banking industry. The focus of the thesis is the determination of counters and the trade off between the opportunity cost and the service level offered by the bank. First, data related to waiting lines was obtained from the QMS system of Bank XYZ. This data includes all costs data required in this study. Questionnaires were also distributed to customers of Bank XYZ to gather information in estimating their opportunity cost. All the data was analysed using various procedures. As an example, the arrival and server pattern was analysed using the K -S test. The result indicates the arrival and server pattern to be Poisson distribution and Exponential distribution respectively. Separate procedures were developed to find optimal number of counters using maximum allowable waiting time and cost model. The result indicates that this method of calculating optimal counters is possible and reliable. The overall result of this study can be repeated and can be easily utilised by other banking institutions in managing their queuing problem.